2007
DOI: 10.1080/10976640600945465
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Myocardial Hyperenhancement on Late Gadolinium-Enhanced Cardiovascular Magnetic Resonance Correlates with Q Waves in Hypertrophic Cardiomyopathy

Abstract: It seems that segmental and transmural extent rather than the mere presence of myocardial LGE is the underlying mechanism of abnormal Q waves in HCM. Additionally, distribution of hypertrophy as indicated by differences in the ratio of septal to posterior wall thickness seems to play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Previous studies attempting to clarify the anatomic basis of Q waves in HC through CMR imaging have yielded conflicting explanations. 30,31 Similarly, we were unable to identify instructive imaging or clinical correlates of these ECG changes in overt HC or G+/LVH− subjects, including LGE as a reflection of gross myocardial scar.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies attempting to clarify the anatomic basis of Q waves in HC through CMR imaging have yielded conflicting explanations. 30,31 Similarly, we were unable to identify instructive imaging or clinical correlates of these ECG changes in overt HC or G+/LVH− subjects, including LGE as a reflection of gross myocardial scar.…”
Section: Discussionmentioning
confidence: 88%
“… 15 21 An abnormal Q wave was determined as described by Konno et al 22 by a Q wave >0.3 mV in depth and/or >0.04 s in duration in at least two leads except aVR. 19 22 …”
Section: Methodsmentioning
confidence: 99%
“… 16 17 In the era of CMR, some studies suggested an association between abnormal Q wave and LGE. 14 18 19 However, few studies compared ECG findings to the mere presence of LGE.…”
Section: Introductionmentioning
confidence: 99%
“…Each segment was visually scored for the total extent of LGE as previously described [19]. The 17 segments were grouped into four cardiac regions: To determine the LGE extent in the septal and lateral regions, the scores of these segments were summed.…”
Section: Lge Quantificationmentioning
confidence: 99%